Whole genome sequencing and metabolomic exploring of a Planococcus spp. isolated from Lake Pastos Grandes for production and characterization of extracellular biopolymers. - (:unkn) unknown (My University, 2026)
In the Lipez region of the Bolivian Altiplano, Lake Pastos Grandes is located at an altitude of 4440 m [2–5] characterized by a short water residence time comparing with other Andean lakes, while most of the lake is composed of salt flats [6–8]. The lake